Estrogen Receptor Beta (ERβ) Expression in Different Subtypes of Malignant Pleural Mesothelioma - Pourdowlat, Guitti; Parvizi, Maryam; Boyadjian, Shogher; Shamaei, Masoud; Pourabdollah, Mihan (Current Respiratory Medicine Reviews, 2022)
Background: Estrogen receptor beta (ERβ) is a potential target for cancer therapy as a tumor suppressor. Malignant pleural mesothelioma (MPM) is a rare but fatal cancer. This study tries to estimate the incidence of ERβ expression in the various subtypes of MPM tumors. Methods and Materials: In a retrospective study performed at a pulmonary tertiary referral hospital, formalin-fixed paraffin-embedded human tissues of 46 definitive MPM were evaluated for expression of ERβ by immunohistochemistry. Results: ERβ was detected in 14 cases (30.4%) out of the total 46 patients with a mean age of 58.08±11.59 SD, including 33 (71.7%) males. There was no statistically significant difference in patients with positive ERβ staining versus negative cases in age and sex (P >0.05). MPM subtypes included 36 (78.2%) cases of epithelioid mesothelioma, 3 (6.5%) cases of sarcomatoid, 5 (10.8%) cases of biphasic, and 2 (4.3%) cases of desmoplastic subtype. ERβ expression was observed only in epithelioid (11 of total 36 cases) and biphasic (3 of total 5 cases) tumors. There was no significant difference in the incidence of ERβ expression in different subtypes of malignant pleural mesothelioma. Statistical analysis shows a significant difference in the expression of ERβ in the epithelioid subtype (with a more favorable prognosis) versus non-epithelioid subtypes (with poor prognosis, including sarcomatoid, desmoplastic, and biphasic) (P = 0.024). Discussion and Conclusion: Considering the higher proportion of the epithelioid type of MPM with ERβ expression, this highlights the role of ERβ in target therapy of MPM tumor, especially in the epithelioid subtype with a more favorable prognosis. A better understanding of the pathology of mesothelioma will eventually contribute to the development of therapies beyond the existing therapeutic platform.
Keywords: Estrogen receptor beta